Perbedaan Tingkat Nyeri Tenggorokan Pasca Ekstubasi Endotracheal Tube (ETT) dan Laryngeal Mask Airway (LMA) di RSUD Dr. Soedirman Kebumen - Shafiyah Rizky Handayani; Tophan Heri Wibowo; Surtiningsih Surtiningsih; Made Suandika (SEHATI: Jurnal Kesehatan, 2024)
General anesthesia is a condition in which the patient loses consciousness completely after taking certain medications. Sore throat is a common complication in postoperative patients with general anesthesia after extubation with laryngeal mask airway or endotracheal tube. The aim of this study was to compare the level of throat pain after extubation using an endotracheal tube versus a laryngeal mask airway. Methods: A quantitative cross-sectional approach was utilized, with accidental sampling as the technique. The study sample comprised 78 respondents who underwent surgery and were extubated with either an endotracheal tube or a laryngeal mask airway at Dr. Soedirman Hospital, Kebumen. Data analysis was conducted using the Mann-Whitney test. Results: Each group, consisting of endotracheal tube and laryngeal mask airway users, had 39 respondents. Throat pain was reported by 34 respondents (84.6%) in the endotracheal tube group and 27 respondents (69.2%) in the laryngeal mask airway group. The Mann-Whitney test yielded a p-value of 0.022, which is less than 0.05. Conclusion: There is a significant difference in the level of sore throat in postoperative patients with the laryngeal extubation technique with the laryngeal mask air way extubation technique and the endotracheal tube extubation technique at dr. Soedirman Kebumen Hospital.